The enigmatic role of IL-38 in inflammatory diseases. (February 2018) - Garraud, Thomas; Harel, Mathilde; Boutet, Marie-Astrid; Le Goff, Benoit; Blanchard, Frédéric
Highlights: IL-38 is an anti inflammatory cytokine from the IL-1F. IL-38 maturation is still poorly understood but is mandatory to exert its biological activity. The receptor for IL-38 is still a matter of debate as it is able to bind 3 different receptor chains. IL-38 might exert its role especially by decreasing the secretion of TH-17 cytokines by macrophages. It is therefore an interesting cytokine to study in TH17 dependent diseases such as psoriatic arthritis. Abstract: IL-38 is the most recently discovered cytokine of the IL-1 family and is considered a potential inhibitor of the IL-1 and Toll-like receptor families. IL-38 exerts anti-inflammatory properties, especially on macrophages, by inhibiting secretion of pro-inflammatory cytokines, leading to reduced T-lymphocyte TH17 maturation. IL-38 has been studied most extensively in the context of chronic inflammatory diseases, particularly arthritis, where it is considered an attractive new drug candidate. IL-38 research has entered a new phase, with the realization that IL-38 is important in the pathophysiology of TH17 dependent-diseases (psoriasis, psoriatic arthritis and ankylosing spondylitis). In this review, we provide a critical evaluation of several controversial issues concerning IL-38 function and regulation. There is effectively contrasting data regarding IL-38: it is produced in conditions such as apoptosis, necrosis or inflammation, but data is lacking regarding IL-38 processing and biological function. Furthermore, the receptor for IL-38 has yet to be identified, although three candidate receptors – IL-1R1, IL-36R and IL-1RAPL1–have been proposed. Future studies will hopefully uncover new aspects of this enigmatic cytokine.